A hingeless Fc fusion system for site-specific cleavage by IdeS. Issue 6 (17th August 2016) - Novarra, Shabazz; Grinberg, Luba; Rickert, Keith W.; Barnes, Arnita; Wilson, Susan; Baca, Manuel
ABSTRACT: Fusion of proteins to the Fc region of IgG is widely used to express cellular receptors and other extracellular proteins, but cleavage of the fusion partner is sometimes required for downstream applications. Immunoglobulin G-degrading enzyme of Streptococcus pyogenes (IdeS) is a protease with exquisite specificity for human IgG, and it can also cleave Fc-fusion proteins at a single site in the N-terminal region of the CH2 domain. However, the site of IdeS cleavage results in the disulfide-linked hinge region partitioning with the released protein, complicating downstream usage of the cleaved product. To tailor the Fc fragment for release of partner proteins by IdeS treatment, we investigated the effect of deleting regions of IgG-derived sequence that are upstream of the cleavage site. Elimination of the IgG-derived hinge sequence along with several residues of the CH2 domain had negligible effects on expression and purity of the fusion protein, while retaining efficient processing by IdeS. An optimal Fc fragment comprising residues 235–447 of the human IgG1 heavy chain sufficed for efficient production of fusion proteins and minimized the amount of residual Ig-derived sequence on the cleavage product following IdeS treatment. Pairing of this truncated Fc fragment with IdeS cleavage enables highly specific cleavage of Fc-fusion proteins, thus eliminating the need to engineer extraneous cleavage sequences. This system should be helpful for producing Fc-fusion proteins requiring downstream cleavage, particularly those that are sensitive to internal miscleavage if treated with alternative proteases.